Criteria for well and layer selection for fracturing–flooding practice in offshore low-permeability reservoirs based on numerical simulation - Tang, Mingguang; Wei, Feng; Ma, Shuai; Deng, Xuan; Zhang, Yuli; Wang, Jinwei; Xing, Tiange; Qiao, Runwei (Frontiers in Earth Science, 2025)
The success in the pilot testing of offshore fracture–flooding provides a new technical idea for the development of low-permeability and under injection oilfields. However, the lack of criteria for well and layer selection has hindered further implementation of fracture–flooding technologies. The establishment of such criteria requires a deep understanding of the production enhancement mechanisms during the fracture–flooding operation. Currently, there is still a lack of a numerical simulation model for fracture–flooding operations that combines the mechanisms of energy replenishment, porosity and permeability increase, crack initiation, and oil displacement using surfactant and imbibition. Furthermore, the influence of individual mechanisms, i.e., how each mechanism contributes to the overall production enhancement, is not quantified. To fill the current knowledge gap in the mechanisms behind fracture–flooding practices, we have conducted experimental studies, established a numerical simulation method for fracture–flooding production enhancement mechanisms, and quantitatively characterized the effects of crack initiation, surfactants, and imbibition during well shut-in. Further studies on establishing the layer selection criteria for fracture–flooding were carried out with the key indexes identified and ranked based on the quantification result of their influence on production enhancement. The results show that the oil-bearing condition has first-order control on production enhancement compared to the physical properties of the reservoir; i.e., it is necessary to ensure that a certain amount of residual reserves exists in the formation first. The established criteria have been tested in the field practice of fracture–flooding, which shows an initial daily oil increase of 50 m3•d−1, and the production capacity of the target layer was increased from 1.2 m3 (d•MPa)-1 to 9.2 m3 (d•MPa)−1, and the cumulative oil increase reached 101,000 mcf in half a year. The field results indicate that the production enhancement effect has met the requirements of the fracture–flooding design. The field practice has proved the feasibility of using our numerical simulation method for the design of fracture–flooding and well/layer selection in the development of offshore low-permeability reservoirs.